Pirates of the Caribbean: dead man's chest - Verbinski, Gore 1964-; Elliott, Ted 1961-; Depp, Johnny 1963-; Knightley, Keira 1985-; Bloom, Orlando 1977- (Walt Disney Home Entertainment, 2006)
Captain Jack owes a blood debt to the legendary Davy Jones, who captains the ghostly Flying Dutchman. Unless Jack can find a way out, he will be cursed to an afterlife of eternal servitude and damnation.
Keywords: Debt - Drama; Deudas - Teatro; Man-woman relationship - Caribbean Sea - Drama; Pirates - Caribbean Sea - Drama; Relaciones humanas - Caribe (Región) - Teatro; Debt -- Drama; Man-woman relationships -- Caribbean Sea -- Drama; Pirates -- Caribbean Sea -- Drama; Film; Action and adventure films; Comedy films; Feature films; Fiction films; Pirate films; Video recordings for the hearing impaired; Adventure - Feature; Adventure films; Comedy - Feature; Feature films - United States